Access to newly functionalized imidazole derivatives: efficient synthesis of novel 5-amino-2-thioimidazoles using propylphosphonic anhydride (®T3P). Issue 8 (18th February 2015) - Lasalle, Manuel; Picon, Sylvain; Boulahjar, Rajaa; Hoguet, Vanessa; Van Obbergen, Jolien; Roussel, Pascal; Deprez, Benoit; Charton, Julie
Graphical abstract: Abstract: We describe here an efficient method to synthesize 5-amino-2-thioimidazole compounds by T3P-mediated cyclization of N -acetamidoisothiourea intermediates. The newly functionalized 5-amino-2-thioimidazole compounds are finally obtained in 5 steps from an amine as starting block.